Strategy Improvement Quality Service Customs Work Obtained Right on Land and Buildings at the Makassar City Regional Revenue - Muh. Nasrullah; Ismail Ismail; Nadila Ramdhani Yusrie (Journal of Public Policy and Local Government (JPPLG), 2025)
Strategy in a way general is plan or the approach used for reach objective certain. Strategy service refers to the approach used by a person organization for give quality and fulfilling services need customer in a way effective and efficient. This study aims to identify strategies that can improve service quality in the Land and Building Acquisition Tax sector at the Makassar City Regional Revenue Agency. Using a qualitative approach, this study utilized data collection techniques such as observation, interviews, and documentation. The results revealed that the strategies implemented by the Land and Building Acquisition Tax at the Makassar City Regional Revenue Agency to improve service quality have been implemented through various methods. This is reflected in several indicators, such as professionalism, responsibility, friendly attitude, the ability to complete tasks on time without complaint, and well-structured procedures. In addition, staff are also actively providing support to customers, providing clear guidance, and ensuring effective, good, and consistent service. In addition, employees also provide adequate information regarding tax payment administration procedures to improve service quality. As one of the office service publics will serve various type daily transactions in give service to people and the performance of BPHTB at the Regional Revenue Agency reflects how much good tax managed, from aspect acceptance, compliance, system support and services public related with transaction land and buildings. Evaluation performance often done for identify obstacle or challenge in collection of BPHTB so that it can repaired.